Effect of concomitant administration of three different antidepressants with vitamin B6 on depression and obsessive compulsive disorder in mice models - Azadeh Mesripour; Valiollah Hajhashemi; Athar Kuchak (Wolters Kluwer Medknow Publications, 2017)
Vitamin B6 is a cofactor of various enzymes influencing numerous neurotransmitters in the brain such as norepinephrin, and serotonin. Since these neurotransmitters influence mood, the aim the present work to evaluate the effect of vitamin B6 on depression and obsessive compulsive behavior when coadministred with clomipramine, fluoxetine, or venlafaxine. Male mice weighing 25-30 g were used. The immobility time and latency to immobility was measured in the forced swimming test as a model of despair and the number of marbles buried (MB) in an open field was used as the model of obsessive compulsive behavior in mice. Vitamin B6 (100 mg/kg, i.p.) was injected to animals for six days and on the last day antidepressants were also administered and the tests took place with 30 min intervals. Immobility was reduced in vitamin B6 + clomipramine (141 ± 15 s) or venlafaxine (116 ± 15 s) but it was not significant comparing with the drugs alone. No beneficial response was seen in co-administration of vitamin B6 with fluoxetine compared to fluoxetine alone. Fluoxetine also increased the latency to first immobility. Vitamin B6 + clomipramine or venlafaxine reduced the MB behaviour by 77 ± 12% and 83 ± 7% respectively, while using them alone was less effective. Fluoxetine was very effective in reducing MB behaviour (95 ± 3.4%) thus using vitamin B6 concomitantly was not useful. Therefore vitamin B6 as a harmless agent could be suggested in depression and particularly in obsessive compulsive disorder as an adjuvant for better drug response.